Students' Learning Strategy in Using YouTube Videos for Self-Regulated Learning - Raffi Augus Syudachi; Yuliana, Yohanes Gatot Sutapa; Surmiyati, Surmiyati (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The objectives of the research were (1) to find out the dominant learning strategy that students employ in using YouTube videos for self-regulated learning and (2) to describe students' learning strategies activity in using YouTube videos for self-regulated learning by tenth-grade students of SMAN 1 Sintang. The data in this research was collected through the instrument of the SILL Questionnaire by Rebeca Oxford which adapted and modified with the context of using YouTube videos for self-regulated learning. The total population of this research was 110 students. The researcher used purposive sampling to select 66 students who were suitable for the characteristics of this study. The research findings revealed that most students used the compensation strategy (19.72%), and the less dominant use strategy was the social strategy (11.66%) in using YouTube videos for self-regulated learning. Specifically, students are greatly helped in using YouTube videos for self-regulated learning by the subtitle feature, and students can also pause the videos to enhance their understanding in finding new vocabulary and phrases, as well as knowing the language structure in the learning videos.